'De-Google-ing' our Students: A User Approach to Understanding Archival Media Discovery in the Classroom - Sabrina Sauer; Berber Hagedoorn; Susan Aasman (VIEW Journal of European Television History and Culture)
This article presents insights about how practices of record-keeping are understood by users of algorithmically curated audiovisual archives in a classroom setting. Our user study looks at the intersection of curated access to digital archives and actual use of these archives, between algorithmic practices and intermediated search. We discuss a pedagogical approach that facilitates learning about the ways in which data-orientated reconfigurations of archival content afford serendipitous information encountering at the data (content) level and the intermediated search (interface) level. This approach requires a ‘de-Google-ing’ (or de-Googling) of student search practices and a move from user-centred to artifact-orientated search regimes.